2021
DOI: 10.1053/j.jfas.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of the Impact of COVID-19 on Telemedicine in the Practice of Foot and Ankle Surgery in the United States

Abstract: In response to loosened telehealth regulations and local restrictions on elective procedures during the COVID-19 pandemic, telemedicine use has dramatically increased. The goal of this study was to analyze patterns in telemedicine use among podiatric physicians during the COVID-19 crisis on a national level. Anonymous responses to a survey of practice metrics as well as subjective impressions of telemedicine efficacy were collected from 246 respondents, representing >1% of practicing podiatrists in the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Depending on the patient's primary chief complaint, various treatment options may be available. In their study, Neville et al 37 did not provide practice guidelines for podiatric telemedicine practice. However, they provided an analysis that revealed podiatrists rated telemedicine as the most effective for prescribing medications and consulting about medical and dermatological issues.…”
Section: Discussionmentioning
confidence: 96%
“…Depending on the patient's primary chief complaint, various treatment options may be available. In their study, Neville et al 37 did not provide practice guidelines for podiatric telemedicine practice. However, they provided an analysis that revealed podiatrists rated telemedicine as the most effective for prescribing medications and consulting about medical and dermatological issues.…”
Section: Discussionmentioning
confidence: 96%
“…Years of clinical practice play a role in ophthalmologists’ satisfaction with VOCs. An orthopedic study conducted by Neville et al reported that years in clinical practice were not statistically associated with the likelihood of offering telemedicine visits post-COVID-19 [ 22 ]. Similarly, 42.3% of ophthalmologists had less than five years of practice experience in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Parisien et al were able to demonstrate that in the United States, the COVID-19 pandemic gave telemedicine services a crucial impetus in academic orthopedic facilities with a positive correlation to the frequency of COVID-19 cases [24]. At 94 %, a dramatic increase in the adoption of telemedicine was also seen among members of the American College of Foot and Ankle Surgeons and the New York State Podiatric Medical Association [25].…”
Section: Discussionmentioning
confidence: 99%
“…Auch Parisien et al konnten zeigen, dass in den Vereinigten Staaten von Amerika die Coronakrise einen entscheidenden Anstoß für telemedizinische Dienste in akademischen orthopädischen Einrichtungen gehabt hatte mit positiver Korrelation zur Häufigkeit der COVID-19-Erkrankungen 24 . Eine dramatische Steigerung bei der Einführung von Telemedizin war auch unter Mitgliedern des American College of Foot and Ankle Surgeons und der New York State Podiatric Medical Association mit einem Anteil von 94% zu sehen 25 .…”
Section: Diskussionunclassified